PEMODELAN SETTLING POND UNTUK PENURUNAN PENCEMARAN KIMIA-FISIK AIR LIMBAH PERTAMBANGAN BATUBARA - Saibun Sitorus; Wahyudin M. (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Making a variety of settling ponds in coal mining is one of the models for reducing the burden of wastewater pollution. This settling pond variation modeling aims to evaluate the ability to reduce the pollution load of wastewater based on chemical quality. The settling pond variation model consists of 3, namely settling pond model 1, model 2 and model 3. The method in this study is descriptive qualitative. Based on the results of the study, the reduction of pollution load on model (1) was 2% (0.0031 kg / second), for model (2) 1.21% (0.4281kg / second) and model (3) 1% (0.0074 kg / second). Actual Pollutant Load -BPA at the settling pond variation site is smaller compared to the Maximum Pollutant Load-BPM (BPA<BPM). Actual pollutant load of settling pond variations (1) 0.107 kg/second, (2) of 0.032 kg/second and (3) 0.105 kg/second. Maximum Pollutant Load (BPM) settling pond (model 1) 0.165 kg/sec, (model 2) 2.01 kg/sec and (model 3) 0.628 kg/sec. The decrease in the load of pollutants in the settling pond is influenced by several factors including vegetation, distance of the source of the pollutant (catchment area) with the settling pond, dimensions of the settling pond (retention pond), the process of giving coagulants, topography, type of lithology. Keywords: Settling pond modeling, pollution reduction, polluting load, Chemical-physical